Pengaruh Penambahan Abu Sekam Padi Pada Tanah Lempung Menggunakan Uji Triaksial - Tiara Ranti Lestari Tiara; Sartika Nisumanti; Ghina Amalia (REKAYASA: Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2025)
Clay soils characterized as soft soils often cause problems due to their weak bearing capacity and long consolidation time. Rice husk ash, which is one of the wastes derived from burning rice stalks and leaves, can be used to increase the bearing capacity of the soil. This research analyzed the effect of adding rice husk ash as a mixture in soil stabilization at 0%, 8%, 12% and 16%. Based on laboratory testing using soil samples from Jalan Merdeka RT 14 Bawah Alai Balai Agung Village, Sekayu District, South Sumatra. Bawah Alai, Balai Agung Urban Village, Sekayu District, South Sumatra. It is concluded that the effect of rice husk ash makes the shear angle of the soil smaller or reduced. The highest shear angle was obtained when the addition of 8% rice husk ash amounted to 9.373 kPa. When adding 12% and 16% rice husk ash, the shear angle of the soil decreased to 4.651 kPa and 4.288 kPa, respectively. The addition of variation in rice husk ash affects the cohesion value (c), overall it can be said that the value of soil shear angle increases with the lower variation in the soil mixture.